2020
DOI: 10.1371/journal.pone.0232621
|View full text |Cite
|
Sign up to set email alerts
|

Possible risk factors for poor asthma control assessed in a cross-sectional population-based study from Telemark, Norway

Abstract: This cross-sectional study of the general population of Telemark County, Norway, aimed to identify risk factors associated with poor asthma control as defined by the Asthma Control Test (ACT), and to determine the proportions of patients with poorly controlled asthma who had undergone spirometry, used asthma medication, or been examined by a pulmonary physician. In 2014-2015, the study recruited 326 subjects aged 16-50 years who had selfreported physician-diagnosed asthma and presence of respiratory symptoms d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
(69 reference statements)
0
16
0
Order By: Relevance
“…The links between obesity and asthma are complex and perhaps best considered to be bi-directional [24]. Poorer asthma control and quality of life, increased corticosteroid use, and emergency service attendance in this patient cohort have been demonstrated in numerous studies worldwide [7,19,20,26,27,31].…”
Section: Asthma and Obesity: Cause And Effectmentioning
confidence: 95%
See 1 more Smart Citation
“…The links between obesity and asthma are complex and perhaps best considered to be bi-directional [24]. Poorer asthma control and quality of life, increased corticosteroid use, and emergency service attendance in this patient cohort have been demonstrated in numerous studies worldwide [7,19,20,26,27,31].…”
Section: Asthma and Obesity: Cause And Effectmentioning
confidence: 95%
“…The association between obesity and asthma has historically been considered uni-directional; people with severe asthma become less active and deconditioned, weight increases, and increased usage of oral corticosteroids (OCS) further aggravates the weight gain cycle. Whilst this cohort of patients undeniably exists, increasing evidence supports the causal link between raised BMI, asthma, and poor asthma control (Table 1 [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]). Cluster cohort studies show a now widely recognised female-predominant obese severe asthma phenotype [38][39][40], particularly affecting peri-and post-menopausal women [37].…”
Section: Asthma and Obesity: Cause And Effectmentioning
confidence: 99%
“…Price et al reported more than 40% of asthma patients used their reliever medications three or more times in the previous week, which the author may judge the reason for the high levels of uncontrolled asthma [ 34 ]. Several studies also reported patients with severe asthma [ 12 , 61 63 ], history of asthma exacerbations/hospitalizations [ 45 , 49 , 53 , 61 , 63 , 64 ], who had comorbid diseases [ 13 , 50 52 , 65 ], smoking [ 43 , 52 , 66 ], oral corticosteroid use [ 12 , 63 ], and irregular follow-up visit [ 56 , 67 ] were more likely had a higher rate of uncontrolled asthma.…”
Section: Discussionmentioning
confidence: 99%
“…There is some previous epidemiological evidence on the determinants of asthma control measured by applying the ACT score. Abrahamsen and colleagues characterized the risk factors for poor asthma control in a cross-sectional study of the general population of Telemark County, Norway [ 5 ]. They used an ACT score ≤ 19 as the measure of poor asthma control.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is substantial epidemiological evidence showing that indoor dampness and mold problems increase the risk of asthma [ 1 , 2 , 3 ]. Furthermore, there is accumulating evidence that some environmental exposures, such as ambient air pollution and chemical exposures from cleaning agents, increase the risk of poor asthma control [ 5 , 6 , 7 , 8 ]. Based on the literature review, we hypothesized that exposure to microbial agents or chemicals from damp structures in residential buildings influences the level of asthma control.…”
Section: Introductionmentioning
confidence: 99%